Barcode technology and emergency medicine pharmacy. (14th December 2016) - Welch, Susan; Samios, Peter
Abstract: Background: The emergency medicine pharmacist (EMP) represents a new field of pharmacy practice in many hospitals and at St Vincent's Hospital Sydney the EMP visits the emergency department (ED) daily Monday to Wednesday (MW), with other pharmacists providing services on Thursday and Friday. Because newer practice areas need to justify services, barcode technology offers an efficient means to collect service provision data. Aim: The aim of this study was to determine whether barcode scanning could be used to efficiently describe and quantify EMP services, including the time involved in undertaking activities. Method: The Activity BarCoding (ABC ® ) system is a commercially available software package that involves using a portable barcode scanner to collect and present data as an activity profile. The ABC ® data generated for the EMP were reviewed for September 2012–March 2013. Results: The MW EMP spent 124.5 h undertaking ED clinical care activities (1.48 h/day). In all, 634 patients were seen and, on average, the MW EMP spent 8.94 min with each patient (range: 6.97–9.93 min). Both clinical and non‐clinical activities could be described, with time allocation and interventions easily quantifiable. Discussion: Barcode technology accurately recorded the variety of and time required for activities performed by the EMP and demonstrated EMP involvement in ED patient care. It provides information that describes and quantifies EMP services that can be used for business case development and service improvements. Further standardisation of activity and intervention categories will enhance data collection, benchmarking possibilities and multicentre research.